2023
DOI: 10.3390/nu15030684
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Honey and Its Effect (Alone as well as with Synthesized Silver Nanoparticles) on Microbial Pathogens’ and Human Cancer Cell Lines’ Growth

Abstract: The antibacterial, anticancer, and wound-healing effects of honey can vary according to the type, geographical region, honey bee species, and source of the flowers. Nanotechnology is an innovative and emerging field of science with an enormous potential role in medical, cosmetics, and industrial usages globally. Metal nanoparticles that derived from silver and range between 1 nm and 100 nm in size are called silver nanoparticles (AgNPs). Much advanced research AgNPs has been conducted due to their potential an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Valued for its broad health-promoting properties, honey has also been studied for its protective influence on liver cells. As a substance produced by bees, it contains secretions from these insects, as well as flower pollen, making it a unique product with an unparalleled chemical composition [ 95 ]. The main immune-stimulating components in honey include proteins, enzymes, and polyphenols [ 95 ].…”
Section: Selected Food Products With Hepatoprotective Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Valued for its broad health-promoting properties, honey has also been studied for its protective influence on liver cells. As a substance produced by bees, it contains secretions from these insects, as well as flower pollen, making it a unique product with an unparalleled chemical composition [ 95 ]. The main immune-stimulating components in honey include proteins, enzymes, and polyphenols [ 95 ].…”
Section: Selected Food Products With Hepatoprotective Propertiesmentioning
confidence: 99%
“…As a substance produced by bees, it contains secretions from these insects, as well as flower pollen, making it a unique product with an unparalleled chemical composition [ 95 ]. The main immune-stimulating components in honey include proteins, enzymes, and polyphenols [ 95 ]. In a study by Hamed A Ghramh et al, the impact of honey and silver-nanoparticle-infused honey on HCC cell growth was beneficial, suggesting that the substance slows down the tumor’s growth processes [ 95 ].…”
Section: Selected Food Products With Hepatoprotective Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, honey mediated green synthesis of nanoparticles expend horizons for new alternative therapeutics. 37,38 These findings exploring micro emulsion formulations and green synthesis of nanoparticles could give new insight to uncover new alternatives to treat breast cancer. The anticancer potency of honey could be either direct or indirect.…”
Section: Anticancer Potencymentioning
confidence: 99%
“…The primary mechanism of action for AgNPs involves their ability to generate increased anticancer activity, induce DNA damage, and cause oxidative stress [ 239 ]. A recent study showed that the combination of honey with AgNPs exhibited the highest efficacy against hepatocellular carcinoma and colon cancer cells [ 243 ]. Similarly, Reddy et al .…”
Section: Introductionmentioning
confidence: 99%